Causal Understanding in Film Viewing: The Effects of Narrative Structure and Personality Traits. (January 2019) - Kovács, András B.; Papp-Zipernovszky, Orsolya
The aim of this research was to investigate the extent to which psychological factors interfere with conscious rational problem-solving in constructing a cinematic narrative's causal connections during film viewing. Talk-aloud protocol was used to record subjects' verbal reactions during watching films. Viewers' texts were analyzed to determine the type and the quantity of causal inferences. This enabled us to determine which parts of the narratives provoked high matching of causal inferences. The results demonstrate recurring correlation between causal thinking and the personality trait openness to experience . In the second study, classical and nonclassical types of narrative were compared in terms of provoking causal inferences. The results demonstrate that classical narrative provokes significantly more causal inferences than nonclassical narrative, and that classical and nonclassical narratives rely equally on personality traits in causal construction.